Tazemetostat in advanced epithelioid sarcoma with loss of INI1/SMARCB1: an international, open-label, phase 2 basket study. Issue 11 (November 2020) - Gounder, Mrinal; Schöffski, Patrick; Jones, Robin L; Agulnik, Mark; Cote, Gregory M; Villalobos, Victor M; Attia, Steven; Chugh, Rashmi; Chen, Tom Wei-Wu; Jahan, Thierry; Loggers, Elizabeth T; Gupta, Abha; et al.
Summary: Background: Epithelioid sarcoma is a rare and aggressive soft-tissue sarcoma subtype. Over 90% of tumours have lost INI1 expression, leading to oncogenic dependence on the transcriptional repressor EZH2. In this study, we report the clinical activity and safety of tazemetostat, an oral selective EZH2 inhibitor, in patients with epithelioid sarcoma. Methods: In this open-label, phase 2 basket study, patients were enrolled from 32 hospitals and clinics in Australia, Belgium, Canada, France, Germany, Italy, Taiwan, the USA, and the UK into seven cohorts of patients with different INI1-negative solid tumours or synovial sarcoma. Patients eligible for the epithelioid sarcoma cohort (cohort 5) were aged 16 years or older with histologically confirmed, locally advanced or metastatic epithelioid sarcoma; documented loss of INI1 expression by immunohistochemical analysis or biallelic SMARCB1 (the gene that encodes INI1) alterations, or both; and an Eastern Cooperative Oncology Group performance status score of 0–2. Patients received 800 mg tazemetostat orally twice per day in continuous 28-day cycles until disease progression, unacceptable toxicity, or withdrawal of consent. The primary endpoint was investigator-assessed objective response rate measured according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary endpoints were duration of response, disease control rate at 32 weeks, progression-free survival, overall survival, and pharmacokinetic and pharmacodynamic analyses (primary results reported elsewhere). Time to response was also assessed as an exploratory endpoint. Activity and safety were assessed in the modified intention-to-treat population (ie, patients who received one or more doses of tazemetostat). This trial is registered with ClinicalTrials.gov, NCT02601950, and is ongoing. Findings: Between Dec 22, 2015, and July 7, 2017, 62 patients with epithelioid sarcoma were enrolled in the study and deemed eligible for inclusion in this cohort. All 62 patients were included in the modified intention-to-treat analysis. Nine (15% [95% CI 7–26]) of 62 patients had an objective response at data cutoff (Sept 17, 2018). At a median follow-up of 13·8 months (IQR 7·8–19·0), median duration of response was not reached (95% CI 9·2–not estimable). 16 (26% [95% CI 16–39]) patients had disease control at 32 weeks. Median time to response was 3·9 months (IQR 1·9–7·4). Median progression-free survival was 5·5 months (95% CI 3·4–5·9), and median overall survival was 19·0 months (11·0–not estimable). Grade 3 or worse treatment-related adverse events included anaemia (four [6%]) and weight loss (two [3%]). Treatment-related serious adverse events occurred in two patients (one seizure and one haemoptysis). There were no treatment-related deaths. Interpretation: Tazemetostat was well tolerated and showed clinical activity in this cohort of patients with advanced epithelioid sarcoma characterised by loss of INI1/ SMARCB1 . Tazemetostat has the potential to improve outcomes in patients with advanced epithelioid sarcoma. A phase 1b/3 trial of tazemetostat plus doxorubicin in the front-line setting is currently underway (NCT04204941 ). Funding: Epizyme.